Un cas rare de pneumopéritoine spontané massif: à propos d’une Observation - Essarghini, Mohamed (Pan Afr Med J, 2017)
Spontaneous pneumoperitoneum is a rare disorder characterized by the presence of free air in the peritoneal cavity, in the absence of any obvious cause. We here report the case of a patient with massive pneumoperitoneum, detected by scan, in whom clinical, biological, radiological and laparoscopic examinations showed no detectable etiology. This case study describes a clinical entity rarely seen in our practice constituting a real diagnostic trap; accurate knowledge about the disease would avoid unnecessary and especially aggressive laparotomies revealing no signs of perforation. The laparoscopy seems to be a minimally invasive surgical procedure for doubtful cases allowing visual diagnosis by eliminating hollow organ perforation.